The Relationship Between Husband's Support and Anxiety Level of Primigravida Pregnant Women in Third Trimester at Puskesmas Gamping I, Sleman Yogyakarta - Rasidah Rasidah; Fayakun Nur Rohmah (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2024)
The first pregnancy for a mother is one of the crisis periods in her life. This anxiety can arise because of the long period of waiting for birth. To decreases mother’s anxiety level, efforts can be made, with support from the husband such as assistance. Lack of trust and support from husbands can result in pregnant women anxiety. The purpose of this study is to determine the relationship between husband support and the anxiety level of primigravida pregnant women third trimester at Puskesmas Gamping I, Sleman, Yogyakarta. The sampling technique used was Accidental Sampling. The population of all pregnant women who made ANC visits at Puskesmas Gamping I in February 1 to May 30, 2023 which amounted to 213 pregnant women and the sample used was 64 pregnant women. Data sources came from primary and secondary data. Data analysis using Univariate and Bivariate. Results of this study showed that of 64 respondents who filled out the questionnaire, the majority of 50 pregnant women (78.12%) received husband support. There were 56 pregnant women (87.50%) who did not experience anxiety, while as 8 pregnant women (12.50%) experienced mild anxiety. The conclusion of this research there is a relationship between husband's support and anxiety about childbirth in third trimester primigravida pregnant women at Puskesmas Gamping I, Sleman, Yogyakarta.